The Implementation of Multimedia on Physics Learning Based on Direct Instruction Model in The Topic of Light - Suritno Fayanto; Misrawati Misrawati; Dwi Sulisworo; Hanin Fathan Nurfina Istiqomah; Luh Sukariasih (ILIN Institute Makassar, 2019)
Student physics learning activities have been successfully analyzed through the direct instruction model using multimedia. This study aims to determine the activities and learning outcomes of students using multimedia. The type of this research is action classroom research and subjects are 33 students of eighth-grade Junior High School 5 Kendari. The results of the analysis show that the direct instruction model using multimedia in physics learning is very suitable for use in the learning process. This can be seen of the learning process among cycle 1 and cycle 2 averaging standards with good categories. It means that the learning outcomes could be improved by using multimedia. This is indicated by the score of students who have increase from cycle I to cycle II. The average score of learning outcomes in the first cycle is 63.73 with a percentage of 54.54%. While the average learning outcomes of the second cycle increased to 73.19 with a percentage of 78.78%.